2013
DOI: 10.1055/s-0032-1333304
|View full text |Cite
|
Sign up to set email alerts
|

Fehler und Gefahren: Behandlung gutartiger Kehlkopferkrankungen

Abstract: More than half of patients who present with the symptom of hoarseness show benign vocal fold changes. The clinician should be familiar with modern diagnostic and therapeutic possibilities of benign vocal fold changes in order to ensure an optimal and individualized attention to voice patients. Basic knowledge of the etiology are provided for targeted phonosurgical or conservative therapy. This review article focuses on the diagnostic and therapeutic limitations and difficulties of treatment of benign vocal fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…[ 23 ] Additionally, increased vascular permeability, degeneration, hypoxia, local edema, and fibrosis may contribute to the development of VFPs. [ 24 ] Changes in the microcosmic, macroscopic, and immune expression of many individuals with VFPs have been attributed to other factors such as traumatic voice behavior, smoking, and apoptosis. [ 25 ] Nonetheless, previous studies have shown that the formation of VFPs in many patients is related to GERD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] Additionally, increased vascular permeability, degeneration, hypoxia, local edema, and fibrosis may contribute to the development of VFPs. [ 24 ] Changes in the microcosmic, macroscopic, and immune expression of many individuals with VFPs have been attributed to other factors such as traumatic voice behavior, smoking, and apoptosis. [ 25 ] Nonetheless, previous studies have shown that the formation of VFPs in many patients is related to GERD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that pepsin in throat epithelial cells could lead to the lack of 2 kinds of protective proteins (carbonic anhydrase isoenzyme III and Sep 70), resulting in damage to the laryngeal mucosa [23] . Additionally, increased vascular permeability, degeneration, hypoxia, local edema, and fibrosis may contribute to the development of VFPs [24] . Changes in the microcosmic, macroscopic, and immune expression of many individuals with VFPs have been attributed to other factors such as traumatic voice behavior, smoking, and apoptosis [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Полипы голосовых складок чаще встречаются у мужчин (55%), представляют собой, как правило, односторонний пролиферативный процесс в области свободного края голосовых складок и составляют от 30 до 70% всех причин нарушения голоса [9]. В 51-90% возникновению полипов голосовых складок способствует курение [10], а также хроническое воспаление и фонотравма, в том числе микротравма слизистой оболочки, приводящая к нарушению микроциркуляции, локальному отеку и воспалению вследствие неправильного голосоведения [10,11].…”
unclassified
“…Отдельно выделяют такой вид полипозной дегенерации голосовых складок, как отечно-полипозный ларингит Рейнке-Гайека, развитие которого ассоциировано с курением и чаще встречается у женщин (80%) от 40 до 60 лет [11]. Для данной патологии характерно поражение мембранозной части голосовых складок, что указывает на недостаточность дренажной лимфатической системы субэпителиального пространства и проявляется дисфонией.…”
unclassified